Bio-orthogonal click reaction-enabled highly specific in situ cellularization of tissue engineering scaffolds. (February 2020) - Mao, Duo; Zhang, Chuangnian; Kenry,; Liu, Jing; Wang, Xiaoxiao; Li, Binhan; Yan, Hongyu; Hu, Fang; Kong, Deling; Wang, Zhihong; Liu, Bin
Abstract: Tissue engineering generally utilizes natural or synthetic scaffolds to repair or replace damaged tissues. However, due to the lack of guidance of biological signals, most of the implanted scaffolds have always suffered from poor in vivo cellularization. Herein, we demonstrate a bio-orthogonal reaction-based strategy to realize in situ specific and fast cellularization of tissue engineering scaffold. DBCO-modified PCL-PEG (PCL-PEG-DBCO) polymer was synthesized and then fabricated into PCL-PEG-DBCO film through electrospinning. Meanwhile, azide-labeled macrophages (N3 (+) macrophages) were obtained through metabolic glycoengineering. Through a series of in vitro dynamic and in vivo characterization, DBCO-modified films were noted to dramatically increase the selective capture efficiency and survival rate of N3 (+) cells. Additionally, there is negligible influence of covalent conjugation on cell viability and proliferation, indicating the feasibility of the bio-orthogonal click reaction-based tissue engineering strategy. Overall, this work shows the advantages of an in situ bio-orthogonal click reaction in realizing highly specific, efficient, and long-lasting scaffold cellularization. We anticipate that this general strategy would be widely applicable and useful in tissue engineering and regenerative medicine in the near future. Graphical abstract: A biorthogonal reaction-based tissue engineering strategy has been developed to realize in situ specific and fast cellularization of scaffold based on combined DBCO-modified PCL-PEG and azide group labeled macrophages. This work exhibits a simple, easy and efficient approach for improving cellularization in regenerative medicine. Image 1